(untitled) (Research, Society and Development, 2026)
This study aimed to evaluate the impact of the Human Milk Bank on promoting breastfeeding, as well as its effects on the survival and clinical recovery of newborns admitted to the Neonatal Intensive Care Unit (NICU). This is a descriptive study with a quantitative approach, developed based on secondary data from the Production System of the Brazilian Network of Human Milk Banks, referring to the period from 2020 to 2024. The results showed a significant volume of human milk collected and broad coverage in all Brazilian regions. The Southeast region concentrated the largest volume of collection and number of donors, while the Northeast region presented the largest number of newborns benefited, highlighting the relevance of the Human Milk Bank in contexts of greater social vulnerability. The findings demonstrate the effectiveness of the Brazilian Network of Human Milk Banks as a strategy to support breastfeeding and safe nutritional care for newborns at risk, especially premature and low birth weight infants. It is concluded that the Human Milk Bank is an essential public policy for neonatal care, contributing significantly to clinical recovery, reducing neonatal morbidity and mortality, and humanizing care in the NICU. Strengthening and expanding the Brazilian Network of Human Milk Banks is fundamental for promoting health equity and improving neonatal outcomes in Brazil.